Development of portable PV generated power supply - Muhammad Farhan, Zainuddin (2012)
Photovoltaic or in short term PV is one of the renewable energy resources that recently has become broader in nowadays technology. The demand or future work is looking for high efficiency, more reliable and economical price PV charge controller which is come in portable size has become very popular in PV system. In general, PV system consists of a PV array, charge controller, rechargeable battery and dc load. PV charge controller is very important in PV system because to control the voltage charging and also to keep the battery from overcharging. In this project, microcontroller (PlC 16F688) are used to monitoring the voltage of the battery. This project used dc-dc buck converter circuit which has been simulated using software of Proteus 7. Liquid Crystal Display (LCD) is used to display the voltage from rechargeable battery. The benefit of this project is an improvement of efficiency voltage change.